Evaluation of a conjugate vaccine platform against enterotoxigenic Escherichia coli (ETEC), Campylobacter jejuni and Shigella. Issue 45 (29th October 2018) - Laird, Renee M.; Ma, Zuchao; Dorabawila, Nelum; Pequegnat, Brittany; Omari, Eman; Liu, Yang; Maue, Alexander C.; Poole, Steven T.; Maciel, Milton; Satish, Kavyashree; Gariepy, Christina L.; Schumack, Nina M.; et al.
Abstract: Enterotoxigenic Escherichia coli (ETEC), Campylobacter jejuni (CJ), and Shigella sp. are major causes of bacterial diarrhea worldwide, but there are no licensed vaccines against any of these pathogens. Most current approaches to ETEC vaccines are based on recombinant proteins that are involved in virulence, particularly adhesins. In contrast, approaches to Shigella and CJ vaccines have included conjugate vaccines in which Shigella lipopolysaccharides (LPS) or CJ capsule polysaccharides are chemically conjugated to proteins. We have explored the feasibility of developing a multi-pathogen vaccine by using ETEC proteins as conjugating partners for CJ and Shigella polysaccharides. We synthesized three vaccines in which two CJ polysaccharides were conjugated to two recombinant ETEC adhesins based on CFA/I (CfaEB) and CS6 (CssBA), and LPS from Shigella flexneri was also conjugated to CfaEB. The vaccines were immunogenic in mice as monovalent, bivalent and trivalent formulations. Importantly, functional antibodies capable of inducing hemaglutination inhibition (HAI) of a CFA/I expressing ETEC strain were induced in all vaccines containing CfaEB. These data suggest that conjugate vaccines could be a platform for a multi-pathogen, multi-serotype vaccine against the three major causes of diarrheal disease worldwide.